Feasibility Analysis of Rice Farming : Case Study on the Detu Janga Farmers Group, Bhera Village, Mego District, Sikka Regency (International Forum of Researchers and Lecturers, 2025)
Observations conducted in the Detu janga group in Bhera village, Mego sub-district, indicated that rice cultivation was feasible. This method was conducted by interviewing 25 farmers as respondents. Analysis was conducted on the components of production costs, total revenue and income, and feasibility and business through R/C calculations and ratios. The interview results showed that production costs for rice crops were Rp 7,130,000.00, while income costs were Rp 10,500,000.00 and overall business income per planting season was Rp 3,370,000.00. The R/C ratio value of 1.48 means >1 and is feasible to cultivate.